Nilai Perusahaan: Implikasi Profitabilitas dan Ukuran Perusahaan - Putri, Melisa Ariani; Aryansyah, Ary Fakturrachman (Universitas Batanghari, 2024)
This research reveals the relationship between profitability and company size on firm value. The research type is quantitative research. The population in this study is companies in the energy sector listed on the Indonesia Stock Exchange. The analysis method used is Multiple Linear Regression Analysis with Smart PLS 4.0 program. The results of this study indicate that profitability has a negative effect on firm value, while company size has no effect on firm value.